DOP50 Effect of upadacitinib on extra-intestinal manifestations in patients with moderate to severe Crohn's disease: data from the CELEST study. (25th January 2019) - Peyrin-Biroulet, L; Danese, S; Louis, E; Higgins, P D R; Dubinsky, M; Cataldi, F; Zhou, Q; Lee, W-J; Kligys, K; Lacerda, A P
Abstract: Background: Extra-intestinal manifestations (EIMs), such as arthropathy, are common in patients with Crohn's disease (CD). 1 The efficacy of Janus Kinase (JAK) inhibition on EIMs is not known in CD. We assessed the prevalence of EIMs at baseline (BL) and the changes over time in EIMs with upadacitinib (UPA), an oral, selective JAK1 inhibitor in the CELEST study. Methods: CELEST was a multi-centre, randomised, double-blind, placebo-controlled, Phase 2 study in adults with moderate-to-severe CD and inadequate response/intolerance to immunosuppressants or tumour necrosis factor inhibitors (TNFi). Patients were randomised to 16-week induction therapy with placebo or UPA 3-, 6-, 12-, or 24-mg twice-daily (BID) or 24-mg once-daily (QD). The presence of EIMs (axial and/or peripheral arthropathy, episcleritis/uveitis/iritis, oral aphthous ulcers, erythema nodosum, pyoderma gangrenosum, Sweet's syndrome, anaemia, auto-immune hepatitis, bronchiectasis, chronic obstructive pulmonary disease, nephrolithiasis, primary sclerosing cholangitis, venous thromboembolism) was collected at BL and Week 16 based on medical interview and physical examination; Fisher exact test was used to compare the UPA groups to placebo for any EIM, classic EIMs (axial and/or peripheral arthropathy, episcleritis/uveitis/iritis, oral aphthous ulcers, erythema nodosum, pyoderma gangrenosum, Sweet's syndrome), and arthropathy. Resolution of EIMs was analysed in patients who had EIMs at baseline and was defined as zero EIMs at Week 16; patients with missing Week 16 data were classified as not resolved. Results: Among 220 randomised patients, 111 (50.5%) had at least one EIM at BL and 31 (28%) of these had two or more EIMs. Patients who had at least one EIM at BL had median (min–max) CD Activity Index (CDAI) 295 (222–447), CD duration 10.8 (0.1–44.7) years, and 85 (96.6%) had failed one or more TNFi. At BL, more patients in the placebo and 3 mg BID groups had at least one EIM compared with UPA 6 and 12 BID, and 24 mg QD. The most commonly reported EIMs were peripheral and/or axial arthropathies ( n = 87), anaemia ( n = 31), and oral aphthous ulcers ( n = 11). At Week 16, compared with placebo, a numerically greater proportion of patients achieved resolution of any EIM, classic EIMs, and arthropathy with UPA 12 and 24 mg BID, and UPA 24 mg QD doses (Table). Conclusions: In this small patient population, a numerical resolution in EIMs was observed with UPA, suggesting a clinical benefit induced by UPA. Reference 1. De Felice K, Raffals LH. Extraintestinal manifestations of Crohn's disease. In: Fichera A, Krane M, editors. Crohn's Disease: Basic Principles . Switzerland: Springer International Publishing; 2015, 245–53.